Effects of Dietary Protein Level during Transition Period on the Performance of Crossbred Heifers - Zaman, Shams Uz; Deka, Raj Jyoti; Barua, Dilip Kumar; Haque, Adib; Saikia, Karuna; Borah, Manish (International Journal of Bio-resource and Stress Management, 2025)
This study was carried out from August to September, 2019 at Instructional Livestock Farm (Cattle) under Department of Livestock Production and Management, College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati (781 022), Assam, India to study the production performance of crossbred heifers during transition period. Twelve pregnant crossbred heifers were selected in advance stage of pregnancy and were divided into two groups 21 days prior to calving viz., Treatment No. 1 (T1) and Treatment No. 2 (T2) consisting six animals in each group. Since 21 days prior to calving, the T1 group was provided concentrate ration having 18% CP and 70% TDN and the T2 group was provided concentrate ration having 22% CP and 70% TDN during the transition period. It was observed that the overall average daily DM intake during pre-partum did not show significant difference due to dietary protein level but during postpartum there was significant difference between the two level of dietary protein. The overall DM intake during postpartum was (10.92±0.27 kg) was significantly higher than pre-partum (6.85±0.16 kg) which might be due to milk production. The average birth weight of calves was not differing significantly. The overall average total blood protein and blood calcium concentration did not show significant difference due to dietary protein level, but there was significant difference between pre-partum and postpartum period. The overall average daily colostrum yield was apparently higher but not significantly higher in T2 than T1 group. From the present study it can be concluded that feeding crossbred heifers with higher dietary protein during transition period improved their production performance.